Work Motivation Category for Harvesters in Afdeling 5, Senyiur Estate, PT. Teladan Prima Agro - Budi Winarni; Subahqul Khoiri; Jamaluddin; Andi Lelanovita Sardianti; Sari Pratiwi; Taman Alex (JURNAL AGRIMENT, 2025)
Motivation is one of the crucial factors that drive individuals to perform optimally, including harvesters who play a vital role in the plantation sector productivity. Harvesting work often involves physically demanding challenges, changing working conditions, and production targets, so their level of motivation greatly affects the efficiency and quality of the harvest. Understanding the categories of work motivation that underlie the enthusiasm of these workers is essential for improving their well-being and ultimately, contributing to sustainability and success of the plantation business as a whole. Objectives of this study are to identify the characteristics of harvesters, measure the categories of work motivation among harvesters, and calculate the productivity of harvesters. This study uses a sample from one population of harvesters at Afdeling 5, Senyiur Estate and employs questionnaires as the data collection tool. Respondent selection technique used a census method, which includes all 30 members of the population. Results show that the highest percentage of harvesters are aged between 31-40 years old (40%), have a primary school education (93%), and have worked for 3-4 years (43%). Work motivation category of harvesters is characterized as ‘very good’. Average productivity of harvesters was shown at 104 bunches/MD, exceeding the company's determined basis (80 bunches/MD).